Gênero, currículo e cultura escolar em uma escola na periferia da zona leste da cidade de São Paulo - Almeida, Marina Oliveira De [UNIFESP] (2019)
Gender relations are constituted as relations of power that permeate inumerous spheres of society, including Education and History teaching. This dissertation intends to analyze how these relations are established in curricular proposals of History in the post redemocratization period in Brazil. We also investigate how these are labeled in a school in the east side of São Paulo, through an ethnographic study of it school culture, to understand theory and practice. Finally, we present a didactic proposal that deals with the idea of diversity, arising from the context of this school.